Estudo e implementação de um protótipo emulador de uma turbina eólica - Costa, Diego Luiz Monteiro (2019)
The present work aims to analyze a wind turbine emulator in a laboratory scale. The purpose of this system was to reproduce on a small scale the disturbances suffered in the generation of wind energy and to analyze in a detailed way these phenomena. In order to the system recognizes the main parameters derived from the wind force caused by the wind turbine, a properly controlled DC (direct current) motor was used, emulating what actually occurs in the wind energy generation system. The properly controlled wind disturbances were noticed at the speed of rotation of the DC motor axis. The generation of electric energy was made by using a three-phase synchronous machine, in the configuration of a generator, which provided the power variations delivered by the motor in the form of alternating voltages and currents. In order to control these voltages and currents provided by the synchronous machine, a three-phase rectifier was built with the objective of transforming the alternating electric quantities to continuous. Allocated the rectifier in series with the synchronous machine was built a DC-DC Boost converter in order to control the power generated by the system. The Boost converter was properly controlled and a Maximum Power Point Tracking (MPPT) technique was implemented. The MPPT technique that best met the characteristics of the system was the technique of P&O (Perturb and Observe) classic. With the extraction of maximum power made in the system, this energy was delivered to a DC busbar that could be used in several applications.